Social responsibility of companies that belong to the program “Em Boa Companhia” of BM&FBOVESPA - Schuster, Herivélton Antônio; Moretti, Bradlei Ricardo; Facin Lavarda, Carlos Eduardo; Klann, Roberto Carlos (Revista de Administração da UFSM, 2016)
The study aimed to identify the level of social responsibility of companies belonging to the “Em Boa Companhia” BM&FBovespa. In this sense, a descriptive and documentary research was conducted, with a quantitative approach. The population of study includes all companies that are part of the “Em Boa Companhia” by BM&FBovespa, listed in the Corporate Sustainability Index (ISE) and Carbon Efficient Index (ICO2), being composed by 29 companies, which six constituted the sample, those had the necessary data. The data analysis was carried out based on the indicators proposed in the Social Balance of the Brazilian Institute of Social and Economic Analysis (IBASE) Model. The results showed that Bank of Brazil was the one that had the highest investment in internal social indicators, while Ultrapar was the one that less invested. Cemig company had the highest value in external social indicators and the greater investment if the net revenue is considered. Moreover, among companies that publish their Social Balance Sheet, the amount of the investments with environmental indicators is significantly lower the internal and external indicators. In addition, most of the amount invested in external indicators is intended for taxes.